The Characteristics of Opportunistic Infections Among AIDS Patiaents in BRSU Tabanan in 2019 - Putu Prayoga Ratha (WMJ (Warmadewa Medical Journal), 2019)
According to WHO and UNAIDS report, there has been dramatic increase of HIV/AIDS cases in Indonesia. The objective of the study was to determine the distribution of opportunistic infections in people with HIV / AIDS and the use of antiretroviral drugs in the BRSU Tabanan from April to June 2019. Data revealed that the number of cases was as many as 126 patient which 55.6% were men and 44.4% were women. The highest age group was 30-39 years (39.4%), and 60.3% of patients still actively working , while the level of education mostly (58.7%) was moderate. Most of the patient (68.2%) were married and 79.3% of patients had CD4 levels